Improving film quality using software solutions in photography studios - Nur Kamila, Idris; Nurhaizan, Mohd Zainudin; Rahimi, A. Rahman (Penerbit Universiti Malaysia Pahang, 2024)
The purpose of this case study was to explore how software solutions can be utilised to improve film quality in photography studios. It focused on the issues faced by a photography studio located in Kangar, Perlis, such as dirty images and damaged films. A survey was administered to 51 working photographers to elicit important insights regarding user preferences and experiences, allowing for a more in-depth grasp of their needs and expectations. The findings revealed that software solutions can be utilised to enhance various aspects of film production, including image clarity, colour accuracy, noise reduction, and overall aesthetic appeal. It also addressed the issue of software flaws and application malfunctions, emphasising the need to use dependable software to avoid disruptions and improve photo editing quality. Photography studios are recommended to combine both high-quality equipment and software programs to optimise business operations, improve overall film quality, and ultimately increase client satisfaction.